Characterization of Fe and Al in Fine Soil Fractions using Selective Dissolution Techniques, X-ray Diffraction and Mössbauer Spectroscopy - Acebal, Silvia (2001)
The fact that partial or complete removal of poorly crystalline iron and aluminum oxides and oxy-hydroxides leads to particle dispersion in soils, suggests that Fe and Al amorphous colloid compounds play an important role in soil-aggregation processes.In order to understand the role of these compounds in soil-aggregation processes three different particle-sizefractions, from the A horizon of an Entic Haplustoll from Bordenave (Argentina), were chemically treated for selective dissolution before characterization techniques like X-ray diffraction and Mössbauer spectroscopy were applied.